Relationship between Streptococcus mutans expressing Cnm in the oral cavity and non-alcoholic steatohepatitis: a pilot study. Issue 1 (1st October 2019) - Tonomura, Shuichi; Naka, Shuhei; Tabata, Keiko; Hara, Tasuku; Mori, Kojiro; Tanaka, Saiyu; Sumida, Yoshio; Kanemasa, Kazuyuki; Nomura, Ryota; Matsumoto-Nakano, Michiyo; Ihara, Masafumi; Takahashi, Nobuyuki; et al.
Abstract : Background: Non-alcoholic steatohepatitis (NASH) is a severe state of non-alcoholic fatty liver disease (NAFLD), which is pathologically characterised by steatosis, hepatocyte ballooning, and lobular inflammation. Host–microbial interaction has gained attention as one of the risk factors for NASH. Recently, cnm -gene positive Streptococcus mutans expressing cell surface collagen-binding protein, Cnm ( cnm -positive S. mutans ), was shown to aggravate NASH in model mice. Here, we assessed the detection rate of cnm -positive S. mutans in oral samples from patients with NASH among NAFLD. Methods: This single hospital cohort study included 41 patients with NAFLD. NASH was diagnosed histologically or by clinical score. The prevalence of cnm -positive S. mutans, oral hygiene and blood tests, including liver enzymes, adipocytokines and inflammatory and fibrosis markers, were assessed in biopsy-proven or clinically suspected NASH among NAFLD. Results: Prevalence of cnm -positive S. mutans was significantly higher in patients with NASH than patients without NASH (OR 3.8; 95% CI 1.02 to 15.5). The cnm -positive S. mutans was related to decreased numbers of naturally remaining teeth and increased type IV collagen 7S level (median (IQR) 10.0 (5.0–17.5) vs 20.0 (5.0–25.0), p=0.06; 5.1 (4.0–7.9) vs 4.4 (3.7–5.3), p=0.13, respectively). Conclusions: Prevalence of cnm -positive S. mutans in the oral cavity could be related to fibrosis of NASH among NAFLD.